Issues of development of competitive relations in the Russian banking system - A. L. Belousov (Russian Journal of Economics and Law)
Objective: to study the features of building competitive relations in the Russian banking sector and to assess the prospects for the development of the system of competition protection regulation in this area.Methods: logical and structural analysis, system-functional approach, formal legal method.Results: the author reveals the essence and features of building competitive relations in the modern banking system of the Russian Federation. Based on the calculation of the Herﬁndahl–Hirschman index, the level of competitive relations in the banking industry is assessed. The key issues, positive and negative trends in the development of competition in the banking sector are identiﬁed. The existing approaches are investigated to the issue of the impact of competition in the banking sector on the stability of both credit institutions in particular and the entire ﬁnancial system as a whole. The inﬂuence of the regulatory mechanism on the state of competition in the banking sector is analyzed. Examples of foreign experience in regulating competitive relations in this ﬁeld are given. The ways of further development of regulatory approaches are formulated, which are aimed at ensuring the protection of competition in the banking system.Scientiﬁc novelty: it consists in the complex nature of the study of relations in competition protection in the banking sector.Practical signiﬁcance: it consists in the formation of a certain theoretical basis necessary both for studying the essence of competitive relations in the banking system and for developing proposals for adjusting regulatory policy in this area in the future.